PERAN LITERASI DIGITAL DALAM PEMBELAJARAN DARING PENDIDIKAN ANAK USIA DINI (PAUD) - Lukman Junaedi; Muchamad Arif; Andini Dwi Arumsari; Natalia Damastuti; Varia Virdania Virdaus (Universitas Narotama, 2023)
The goal of this study was to assess the level of digital literacy proficiency among parents of PAUD students in the Ngawi Regency. The research was conducted using a mixed-methods approach and benchmarked against prior studies of a similar nature on parental digital literacy and online learning at the PAUD level under the new normal. The study's findings included data from 30 PAUD who participated as respondents and represented 30 subdistricts in the Ngawi Regency. Based on the survey's findings, it is known that the majority of PAUD-level online learning processes still use message-based communication via SMS or Whatsapp media instead of digital learning platforms. Numerous PAUD schools have attempted to teach using digital platforms like Zoom, Google Meet, Microsoft Team, but their efforts have been limited by students' low levels of computer proficiency and parents' limited availability. This demonstrates that despite the fact that practically all parents are accustomed to utilizing mobile devices and other digital communication tools for communication, they do not know how to utilize them for learning. According to the study's findings, in order to support the success of learning programs and activities, particularly those conducted online due to the ongoing COVID-19 pandemic, policies and guidelines for digital literacy must concentrate on improving parents' knowledge of and capacity for access to digital learning systems. Keywords: Digital Literacy, Online Learning, PAUD, Covid-19